2018
DOI: 10.1155/2018/9434385
|View full text |Cite
|
Sign up to set email alerts
|

Grape Seed Proanthocyanidin Ameliorates Cardiac Toxicity Induced by Boldenone Undecylenate through Inhibition of NADPH Oxidase and Reduction in the Expression of NOX2 and NOX4

Abstract: The effect of anabolic androgenic steroids on the cardiovascular system is poorly understood. Increased production of free radicals is coupled to the pathophysiology of many alterations within the circulatory system. The only function of the enzyme family NADPH oxidases (NOXs) is the generation of reactive oxygen species (ROS). Therefore, this study investigated the beneficial role of grape seed proanthocyanidin extract (GSPE) in ameliorating cardiac toxicity induced by the anabolic steroid Boldenone in male r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 55 publications
4
32
1
Order By: Relevance
“…Furthermore, grape polyphenols were shown by a large number of in vitro, animal, and human studies to have a positive effect on prevalent cardiovascular risk factors [34]. e findings of this study were consistent with those reported by Tousson et al [15], who observed that cardiac toxicity caused by boldenone undecylenate was attenuated by GSPE by suppressing NADPH oxidase and downregulating NOX2 and NOX4 expression. Moreover, based on rodent models, GSPE has been demonstrated by Karthikeyan et al [35] to confer effective cardiac protection by ameliorating myocardial damage caused by isoproterenol.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, grape polyphenols were shown by a large number of in vitro, animal, and human studies to have a positive effect on prevalent cardiovascular risk factors [34]. e findings of this study were consistent with those reported by Tousson et al [15], who observed that cardiac toxicity caused by boldenone undecylenate was attenuated by GSPE by suppressing NADPH oxidase and downregulating NOX2 and NOX4 expression. Moreover, based on rodent models, GSPE has been demonstrated by Karthikeyan et al [35] to confer effective cardiac protection by ameliorating myocardial damage caused by isoproterenol.…”
Section: Discussionsupporting
confidence: 91%
“…us, the control group (G1) consisted of mice that were not treated in any way. e GSPE group (G2) consisted of mice that were administered daily by oral gavage 50 mg/kg GSPE over a period of 14 days [15]. e EST group (G3) consisted of mice that carried EST for a period of 14 days [16].…”
Section: Experimental Design and Animal Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…A regulatory complex comprising three protein subunits with different gene encoding, troponin is found on the thin filament of the myocardial contractile mechanism. It is the main biomarker for diagnosing myocardial infarction [43] because increase in its level is exclusively indicative of cardiac damage, whereas increase in CK-MB is not [9,16]. Sorodoc et al [44] reported on a case where all three aspects for diagnosing acute myocardial infarction were present, namely, clinical symptoms, electrocardiographic alterations, and increased levels of the myocardial enzymes CK and CK-MB.…”
Section: Discussionmentioning
confidence: 99%
“…As the latest discoveries suggest, hypertension, lipid metabolism changes, and other cardiovascular complications occur primarily as a result of oxidative stress. When reactive oxygen species (ROS) are generated in excess, oxidative stress can promote the development of different disorders, including cancer, neurodegenerative conditions, ageing, and CVDs [16,25,26]. Given the above considerations, this work employed L-NAME-induced rats with hypertension to determine how SA affected cardiac functions and structure as well as enzymatic antioxidants and lipid profile levels.…”
Section: Introductionmentioning
confidence: 99%